Building a Future Saving Science Paradigm - Rahma, Cut Dewi; Walidin, Warul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The future-saving science paradigm from an Islamic perspective offers a holistic and ethical approach in dealing with global challenges such as climate change, resource shortages, and social inequality. This research aims to integrate scientific principles with Islamic teachings that emphasize balance, sustainability, and justice. The method used is literature analysis with a qualitative approach to explore Islamic principles in science and technology. Data collection techniques through the use of document study method, which involves analyzing documents relevant to the topic under study. The results of the study provide an explanation that Islamic teachings that prioritize tawhid (oneness of God), khilafah (stewardship of the earth), and maslahah (public good) can be the basis for the development of science that is oriented towards environmental sustainability and human welfare. This new paradigm should focus on multidisciplinary integration, ethics and community engagement in order to create sustainable and relevant solutions. The importance of interdisciplinary collaboration will help generate more comprehensive innovations in solving interrelated problems. Thus, this science paradigm transformation is not only essential for the preservation of the earth, but also for creating a just and harmonious future in accordance with Islamic values. The proposed science paradigm is not only based on rationality but also spirituality, creating a model of science that is more just, harmonious, and in line with Islamic values for the sustainability of the earth and human welfare.